Seasonality of influenza and coseasonality with avian influenza in Bangladesh, 2010–19: a retrospective, time-series analysis. Issue 8 (August 2022) - Berry, Isha; Rahman, Mahbubur; Flora, Meerjady Sabrina; Shirin, Tahmina; Alamgir, A S M; Khan, Manjur Hossain; Anwar, Rubaid; Lisa, Mona; Chowdhury, Fahmida; Islam, Md Ariful; Osmani, Muzzafar G; Dunkle, Stacie; et al.
Summary: Background: Seasonal and avian influenza viruses circulate among human and poultry populations in Bangladesh. However, the epidemiology of influenza is not well defined in this setting. We aimed to characterise influenza seasonality, examine regional heterogeneity in transmission, and evaluate coseasonality between circulating influenza viruses in Bangladesh. Methods: In this retrospective, time-series study, we used data collected between January, 2010, and December, 2019, from 32 hospital-based influenza surveillance sites across Bangladesh. We estimated influenza peak timing and intensity in ten regions using negative binomial harmonic regression models, and applied meta-analytic methods to determine whether seasonality differed across regions. Using live bird market surveillance data in Dhaka, Bangladesh, we estimated avian influenza seasonality and examined coseasonality between human and avian influenza viruses. Findings: Over the 10-year study period, we included 8790 human influenza cases and identified a distinct influenza season, with an annual peak in June to July each year (peak calendar week 27·6, 95% CI 26·7–28·6). Epidemic timing varied by region ( I 2 =93·9%; p<0·0001), with metropolitan regions peaking earlier and epidemic spread following a spatial diffusion pattern based on geographical proximity. Comparatively, avian influenza displayed weak seasonality, with moderate year-round transmission and a small peak in April (peak calendar week 14·9, 95% CI 13·2–17·0), which was out of phase with influenza peaks in humans. Interpretation: In Bangladesh, influenza prevention and control activities could be timed with annual seasonality, and regional heterogeneity should be considered in health resource planning. Year-round avian influenza transmission poses a risk for viral spillover, and targeted efforts will be crucial for mitigating potential reassortment and future pandemic threats. Funding: Canadian Institute of Health Research Vanier Canada Graduate Scholarship.